Mapping the Conditions of Poetry Learning Media in Junior High Schools Based on the Perspective of Cognitive Load Theory - Nugroho, Rudi Adi; Taufik, Indra Nugrahayu; Puspita, Yulia; Noh, Nurulrabihah Mat (IJORER : International Journal of Recent Educational Research, 2026)
Objective: This study looks at how Indonesian junior high school teachers use instructional media when teaching poetry, with the analysis grounded in the principles of Cognitive Load Theory (CLT). The data were drawn from teachers’ lesson plans and teaching modules to understand what kinds of media they choose, how they make those decisions, and how students respond during learning. Method: This study employed a descriptive qualitative design with document analysis as the primary method. The design was chosen to systematically examine teachers’ instructional documents and identify patterns in the use of media for poetry learning. Results: A total of 68 teaching modules were collected. Videos appear to be the most widely used (94.1%), followed by visual materials such as images or diagrams (72.1%). The use of digital tools such as YouTube, Canva and Quizizz appears to support germane cognitive load. These tools help students to develop schemas, promote active engagement, and provide opportunities for learners to connect new information with their prior knowledge. The combination of multimodal content and contextual examples contributes to more meaningful learning experiences in the poetry classroom. Novelty: Learning media should not only attract students’ attention but also function as cognitive support that helps them manage the complexity of poetic texts. The integration of multimodal resources and digital platforms, when aligned with the principles of Cognitive Load Theory, points to a promising direction for improving the quality of poetry teaching.